The Effect of Modified Media on The Antibacterial Activity of The Sea Sponge Symbion Fungi, Fusarium solani - Muslihuddin Aini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The purpose of this study was to analyze the biomass production and bioactivity of sponge symbiont mushroom extracts on modified media using experimental laboratory methods. Biomass was calculated by weighing the wet weight of the symbiont mushroom mycelium and then tested for antibacterial activity with an extract concentration of 500 µg/disk. The results of this study, namely the weight of F.solani mycelium on MKD + MGV media was 10 grams, the mass of mycelium on MKD media was 9 grams, while the mass of mycelium on MEB standard media was 9.7 grams. The yield weight of the F.solani crude extract cultured on MKD + MGV media was 0.0386 grams or 0.3860% of the wet weight, on MKD media it showed that the crude extract weight was 0.0276 grams or 0.3067% of the wet weight, while on MEB the crude extract weight was 0.0119 grams or 0.1190% of the wet weight. The results of the antibacterial test showed that the largest inhibition zone for MDR (Meticilin Resistant Staphylococcus aureus) bacteria was F.solani crude extract cultured on MKD + MGV media, namely 25.83 ± 3.37 mm, F.solani cultured on MKD media of 22.10 ± 2.51 mm , while F. solani cultured on MEB media was 19.00 ± 0.52 mm. The results of the mass culture of the fungus Fusarium solani on modified media showed that the mushrooms cultured on MKD + MGV media had greater biomass, crude extract and antibacterial activity compared to MKD and MEB culture media.